PERSEPSI CALON GURU PAI TERHADAP KOMPETENSI 6C DALAM MENGHADAPI ERA 4.0 - Fikri, Ali; Rahmawati, Aulia; Hidayati, Nur (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
In the 4.0 era, technology was rapidly developing which caused changes in the perspective of education. The competencies needed in the world of education are also changing. This affects the competency of prospective teachers. They must prepare, improve, and continue to hone their competencies to be able to produce a quality generation that is able to answer the challenges in the current 4.0 era. This study aims to explain the perceptions of prospective PAI teachers, inform about 6C competencies which is an update in the 4.0 era curriculum which was formerly known as 4C competencies but now gets two additional new competencies by the Minister of Education and Culture so that they become 6C competencies, as well as challenges faced by prospective PAI teachers in era 4.0. The method used in this research is descriptive qualitative method and literature study. The results and discussion of this research are found that: 1. From the perception of PAI teacher candidates many do not know about the 6C competency being promoted by the Minister of Education and Culture because it has not been a focus among educators. 2. Prospective educators try to hone their competencies to face the 4.0 era.